Parents’ acceptance towards the use of dental therapist in the private sector – a quantitative study - Zakaria, Noor Azhani; Ab Murat, Norintan; Che Musa, Muhd Firdaus (2019)
Objectives: To assess parents’ acceptability towards the use of dental therapists’ (DT) in providing treatment to children in private settings and to explore factors associated with their perception. Methods: A cross-sectional study was conducted among 1260 randomly selected parents of 11 years old schoolchildren in Selangor. A self-administered structured questionnaire was used, which consisted of three sections: sociodemographic characteristics, dental service utilisation and acceptance towards DT in providing seven types of preventive and operative dental procedures. Data were analysed using SPSS version 22.0 software using both descriptive and inferential statistics. The p-value was set at <0.05. Results: The response rate was 83.1%. Overall, perceived acceptance among the parents ranging from (62.0%) for ‘deciduous teeth extraction’ to (87.7%); for ‘receive oral hygiene education’ of all procedures. Four out of seven dental procedures performed by DT were rated as high acceptance (>70%). Almost three-quarter (71.4%) of parents having high acceptance; accept more than or equal to five procedures. In multivariate analysis, parents who have high acceptance were those who were younger (OR=1.71, 95% CI= 1.26-2.32), lived in urban (OR=1.71, 95% CI= 1.23-2.36), Bumiputra in origin (OR=1.92, 95% CI= 1.08-3.43). However, mothers (OR=0.71, 95% CI= 0.52-0.95). and those who were unsure the presence of dental clinic nearby their home (OR=0.45, 95% CI= 0.24-0.87) were less likely having high acceptance. Conclusion: This study pointed out parent’s have high acceptance towards DT in providing treatments to their children in the private dental clinics and were associated with their sociodemographic status.